The relationship between moral distress, resilience, and job burnout among nurses - Rasool Solaimani Moghaddam; Fatemeh Samiei; Tahereh Baloochi Beydokhti (Tehran University of Medical Sciences, 2024)
Background & Aim: Nurses, due to the demands of their profession, are frequently exposed to high-stress clinical situations, such as the COVID-19 pandemic, which can lead to moral distress and affect their resilience, ultimately contributing to job burnout. This study aims to investigate the relationship between moral distress, resilience, and burnout among nurses. Methods & Materials: In this descriptive, cross-sectional study, 188 nurses working in hospitals affiliated with the Birjand University of Medical Sciences during the years 2021-2022 were selected through simple random sampling. The data collection tools included demographic information, the Moral Distress Scale, the Davidson Resilience Scale, and the Maslach Burnout Inventory. Data were analyzed using descriptive and inferential statistics in SPSS software version 21. Results: The results indicated that the nurses experienced low moral distress (30.28±12.59), high resilience (63.70±13.44), and high levels of burnout (54.98±12.30). A direct and significant relationship was found between moral distress and burnout, while a weak and significant inverse relationship was observed between moral distress and resilience (P<0.001). Conclusion: Given the significant relationship between moral distress, resilience, and burnout, it is recommended that policymakers develop strategies to enhance resilience, which could lead to a reduction in moral distress and burnout among nurses.